Scuba diving incidence and carrying capacity of dive sites at Jardines de la Reina National Park, Cuba - Hernández-Fernández, Leslie; Olivera-Espinosa, Yunier M.; Figueredo-Martín, Tamara; Gómez-Fernández, Raúl; Brizuela-Pardo, Leander; Pina-Amargós, Fabián (Revista Ciencias Marinas y Costeras, 2016)
Scuba diving is one of the main activities in the Jardines de la Reina National Park (PNJR), located off the southern coast of Sancti Spiritus, Ciego de Avila and Camagüey provinces. This study was conducted to determine the effect of this activity on the coral reefs of the area, particularly on stony corals. A total of 28 sites were surveyed during a ten-day period. Areas with high, medium, and low diving intensity, as well as no diving were compared taking into account the percentage of stony coral cover. A total of 220 line transects were used and 51 divers were observed. In sites with high diving intensity, 36 species of stony corals were identified, mostly including S. siderea, A. agaricites, P. astreoides, M. alcicornis and O. faveolata. Of the 51 divers observed, 48 violated diving regulations such as making contact with the corals, sediment resuspension, and, to a lesser degree, mechanical damage (breaking of organisms). Gorgonians, followed by stony corals, were the most contacted organisms. The amount of touches per diver was 5.8 touches/minute. Effective carrying capacity in PNJR ranged from 15 to 35 divers/site/day. It is inferred that, in spite of the impact of scuba diving recorded on the surveyed sites, the sites showed no signs of deterioration. However, monitoring affected organisms to follow up post-damage evolution and complying with the number of divers/site/day suggested in this study is recommended.